Better Function With a Colonic J-Pouch or a Side-to-end Anastomosis?: A Randomized Controlled Trial to Compare the Complications, Functional Outcome, and Quality of Life in Patients With Low Rectal Cancer After a J-Pouch or a Side-to-end Anastomosis. Issue 5 (May 2019) - Parc, Yann; Ruppert, Reinhard; Fuerst, Alois; Golcher, Henriette; Zutshi, Massarat; Hull, Tracy; Tiret, Emmanuel; Hemminger, Felix; Galandiuk, Susan; Fender, Svenja; Weber, Klaus; Zimmerman, Anton; et al.
Abstract : Background information: We aimed to compare prospectively the complications and functional outcome of patients undergoing a J-Pouch (JP) or a side-to-end anastomosis (SE) for treatment of low rectal cancer at a 2-year time point after resection for rectal cancer. Methods: A multicenter study was conducted on patients with low rectal cancer who were randomized to receive either a JP or SE and were followed for 24 months utilizing SF-12 and FACT-C surveys to evaluate the quality of life (QOL). Fecal incontinence was evaluated using the Fecal Incontinence Severity Index (FISI). Bowel function, complications, and their treatments were recorded. Results: Two hundred thirty-eight patients (165 males) were randomized with 167 final eligible patients, 80 in the JP group and 87 in the SE group for evaluation. The mean age at surgery was 61 (range 29 to 82) years. The overall mean recurrence rate was 12 of 238, 5% and similar in both groups. Complications: Overall, 37 of 190 (19%) patients reported complications, 14 of these were Clavien Dindo Grade 3b and 2 were 3a: leak 3 (2 JP, 1 SE), fistula 4 (1 JP, 3 SE), small bowel obstruction 4 (3JP, 1 SE), stricture 4 (3 SE, 1 SA), pouch necrosis 2 (JP), and wound infection 5 (2 JP, 3 SE). QOL scores using either instrument between the 2 groups at 12 and 24 months were similar ( P > 0.05). Bowel movements, clustering, and FISI scores were similar. Conclusion: At time points of 1 and 2 years after a JP or a SE for low rectal cancer, QOL, functional outcome, and complications are comparable between the groups. Although choosing a particular procedure may depend on surgeon/patient choice or anatomical considerations at the time of surgery, SE functions similar to JP and may be chosen due to the ease of construction.